Estimation of Direct and Diffuse Solar Radiation on Bode, Bhaktapur (Journal of Nepal Physical Society, 2022)
The main objective of the study is to estimate direct solar radiation (IB) and diffuse solar radiation (ID) on Bode, Bhaktapur (27.68° N, 85.39° E, 1297 m a. s. l.) for a period of one year (2013). Daily data of Aerosol optical depth (AOD), total ozone column are derived from NASA  website. The maximum and minimum monthly average of diffuse solar radiation values were  found 318±95 W/m2 in April and 108 ± 20 W/m2 in August respectively. The maximum and  minimum monthly average of direct solar radiation values were found 975±74 W/m2 in  February and 748 ± 126 W/m2 in March respectively. The annual average of diffuse solar  radiation and direct solar radiation are found 216 ± 88 W/m2 and 864 ± 125 W/m2 respectively. Result of this research work is beneficial for the further identification, impact and analysis of direct solar radiation diffuse solar radiation at different places.